An Overview of Budget Jurisprudence (Fiqh) to Eradicate the Corruption in Indonesia - Dedi (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyze an overview of the budget jurisprudence concept to eradicate corruption behavior in Indonesia. There is some instrument to understand about Islamic jurisprudence such as Alquran, Hadis, Ijma (consensus), and Qiyas (measuring). The core principles in budget management are transparency, accountability, budgetary discipline, justice, efficiency, and effectiveness. The research was normative law. The data obtained through several sources such as books, journals, and relevant results research. The results showed that the Budget Fiqh contained in tauhid, namely the attitude of a Muslim that he does worship meets the provisions of Allah and will be accounted for in the world and the hereafter. On the other side, the Budget Fiqh requires the Shidq (honest) and amanah (trustworthy) attitude. Shidq is closely related to the budget information process. At the same time, the mandate is related to the commitment to allocate and distribute the budget to those entitled to implement the values of benefit, welfare, goodness, and accountability. This research concludes that in the perspective of budget fiqh, upholding budget transparency is the implementation of worship that occupies a great and noble position in religion.